Environmental collaboration and blockchain technology adoption in green medical supply chain management during the COVID-19 pandemic - Bai, Yang; Song, Wenqi (Frontiers in Environmental Science, 2022)
In recent years, the resource shortage and environmental degradation have made enterprises and governments increasingly aware of the importance of sustainable development. Meanwhile, the COVID-19 pandemic has also increased the shortage of medical materials. Based on this, we build the critical medical device refurbishing strategies with and without blockchain adoption in three different structures: manufacturer refurbishing, retailer refurbishing, and third-part refurbishing in the two-period refurbishing strategies. The manufacturer always benefits from adopting a blockchain technology strategy in all three refurbishing structures. However, the retailer's reference depends on the consumer's willingness to pay φ. Only if the willingness to pay φ is extremely high, the retailer always chooses the blockchain strategy. In the different scenarios with adopting blockchain technology, when the consumer's willingness to pay φ is low, the whole channel always chooses the third-part refurbishing scenario. With φ increasing, the manufacturer refurbishing becomes the optimal choice for the whole channel.